TANGGUNG JAWAB HUKUM PENYELENGGARA SISTEM ELEKTRONIK (LAW RESPONSIBILITY OF THE ELECTRONIC SYSTEM PROVIDERS) - Salam, Abdul (Indonesia Law Review, 2011)
Reviewing Edmon Makarim’s book which is about Law Responsibility of the Electronic System Providers, remind us that easiness and availability of electronic system in electronic transaction in private or public happen because the role of electronic system providers. Behind the important and central role, there is big responsibility for electronic system providers. But because of wide of definition of provision of electronic system and so many people who involve in electronic system providers, there is a question in our mind, how is the shape of responsibility of the electronic system providers if the electronic system which is held is broken and / or not in operation as it has to and bring loss to users. Which one from the electronic system providers should take the responsibility in law?